2011
DOI: 10.3109/15412555.2011.623737
|View full text |Cite
|
Sign up to set email alerts
|

Are We Aware of Restless Legs Syndrome in COPD Patients Who Are in an Exacerbation Period? Frequency and Probable Factors Related to Underlying Mechanism

Abstract: A few previous studies have reported that the patients with chronic obstructive pulmonary disease (COPD) have a 29.1% to 36.8% frequency of restless legs syndrome (RLS). In this study, we observed RLS symptoms in patients experiencing COPD exacerbation to better understand the relationship between the many clinical parameters of COPD and the presence of RLS and to attract the attention of specialists on the association between the two conditions. Twenty-two male patients in COPD exacerbation; 17 healthy indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 47 publications
(43 reference statements)
0
12
0
3
Order By: Relevance
“…RLS symptoms worsen during COPD exacerbations, further affecting sleep. 15 Psychiatric disorders such as depression and anxiety frequently accompany chronic medical disorders. Prevalence rates of up to 80% for depression and 74% for anxiety have been reported in COPD patients.…”
Section: Etiologymentioning
confidence: 99%
“…RLS symptoms worsen during COPD exacerbations, further affecting sleep. 15 Psychiatric disorders such as depression and anxiety frequently accompany chronic medical disorders. Prevalence rates of up to 80% for depression and 74% for anxiety have been reported in COPD patients.…”
Section: Etiologymentioning
confidence: 99%
“…RLS symptomatology was more severe in those patients with COPD and there was an association with increased daytime sleepiness. Further data demonstrated a RLS prevalence of 54.5% in patients during an acute exacerbation of COPD [24]. In a large population-based sample of males and females from Sweden and Iceland, Benediktsdottir and coworkers found a higher prevalence of RLS in subjects Model 2 (adjusted for cardiovascular, metabolic, and psychiatric comorbidities)…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of RLS is approximately 30% to 40% in chronic obstructive pulmonary disease (COPD) patients. 49 An investigation compared COPD patients hospitalized for respiratory exacerbations with healthy volunteers and found that 54.5% of inpatients with COPD exacerbation met criteria for a diagnosis of RLS compared with 5.4% of controls (P 5 .001). 49 The mechanism linking RLS to COPD is unclear; however the previously described data suggest that patients hospitalized for COPD exacerbation may be at high risk.…”
Section: Special Populationsmentioning
confidence: 99%